2016
DOI: 10.1016/j.urology.2016.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Insulin-like Growth Factor-1 Receptor Is Associated With Penile Cancer Progression

Abstract: Objective To evaluate insulin-like growth factor-1 receptor (IGF1R) expression in penile cancer and its association with oncologic outcomes. Methods Tissue microarrays were constructed from 53 patients treated at our institution. Expression of IGF1R was evaluated using a Her2-like scoring system. Overexpression was defined as 1+ or greater membranous staining. Association of IGF1R expression with pathologic features was assessed with comparative statistics, and association with local recurrence, progression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…IGF1R is a transmembrane glycoprotein that is important in a number of biological functions (23). Previous studies have demonstrated that IGF1R is vital in cancer development and progression (24)(25)(26). IGF1R can be used as a novel marker for targeted therapy for several types of tumor, including glioma, colorectal cancer and breast cancer (27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…IGF1R is a transmembrane glycoprotein that is important in a number of biological functions (23). Previous studies have demonstrated that IGF1R is vital in cancer development and progression (24)(25)(26). IGF1R can be used as a novel marker for targeted therapy for several types of tumor, including glioma, colorectal cancer and breast cancer (27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is a risk factor for cancer in general and is associated with an increased risk of invasive penile cancer, inducing chronic inflammation and insulin resistance [ 52 ]. Overexpression of IGF1R was reported by Ball and colleagues (2016) in 62% of a cohort of 53 men diagnosed with penile cancer and was associated with inferior progression-free survival (PFS) [ 53 ]. A comparison between patients without IGF1R overexpression and those with overexpression revealed a significant difference in 5-year PFS rates, with 94.1% versus 45.8%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…This receptor plays a critical role in cell proliferation, differentiation, and malignant transformation. Protein overexpression of IGF1R has been associated with lower disease-free survival in penile cancer ( 47 ).…”
Section: Introductionmentioning
confidence: 99%